Waste‐grown phototrophic bacterium supports culture of the rotifer, Brachionus rotundiformis - Loo, P.L.; Chong, V.C.; Vikineswary, S.; Ibrahim, S. (Blackwell Publishing, 2015)
The present and commonly used batch culture system (BCS) as adopted by many small‐scale tropical hatcheries is beset by poor rotifer production and sudden crashes. This study aimed to produce nutritive rotifers and evaluate their performance based on the BCS by using phototrophic bacteria (PB) that can be easily and cheaply cultured from palm oil mill effluent (POME), an agro‐industrial byproduct usually discarded as waste. Brachionus rotundiformis given a sole diet of POME‐grown PB (Rhodovulum sulfidophilum) grew as well as on the commercially produced microalgae, Nannochloropsis. Production, growth rate and fecundity of rotifers fed condensed bacterial cells (bPB) and culture broth of bacteria grown in POME (cPB) were evaluated. The best performance in terms of the stated parameters was obtained for rotifers fed 200 mL of cPB in 3 L of culture water; this media sustained a mean rotifer density of 600–900 individuals mL−1 after 3–6 days of culture. The biochemical composition of rotifers fed PB was comparable to those fed microalgae, except that the former contained more polyunsaturated fatty acids.